High Pressure Processing of Food Principles, Technology and Applications - Balasubramaniam, V.M.; Barbosa-Cánovas, Gustavo V.; Lelieveld, Huub L.M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
High-pressure processing (HPP) represents an industrially relevant solution to the growing consumer demand for wholesome, fresh-tasting foods, where application of pressure assures food safety. Through 31 chapters grouped into 7 relevant sections, the book comprehensively reviews and summarizes current state-of-the-art knowledge, from process engineering, packaging, industrial scale equipment, consumer acceptance, regulations, to application of high pressure in food pasteurization, sterilization, extraction, homogenization, and freezing and thawing. Food safety specialists and process authorities working in both government and food industry sectors will find useful chapters about pressure effects on harmful biological agents as well as approaches to validation of high pressure technology.  Chapters related to high pressure reaction kinetics, process uniformity, mathematical modeling, pressure effects on proteins, enzymes starch and bioactive co mpounds, and structural changes in pressure treated foods will be particularly beneficial for graduate and undergraduate students to discover the latest information on high pressure preservation principles. Chapters concerning high pressure applications in different food industry sectors will serve as excellent reference to food industry professionals, in particular to those involved in the processing of products such as meat, seafood, beverage, dairy, eggs, fruits and vegetable products. .
Preface -- Section 1. Introduction -- 1. Fundamentals and Applications of High Pressure Processing Technology -- 2. A Short History of Research and Development Efforts Leading to the Commercialization of High Pressure Processing of Food -- Section 2. Process Equipment and Packaging -- 3. Industrial Scale High Pressure Processing Equipment -- 4. Continuous-High Pressure Processing to Extend Product Shelf Life -- 5. High Pressure Effects on Packaging Material -- Section 3. High Pressure Process Engineering Characterization -- 6. In Situ Thermal, Volumetric and Electrical Properties of Food Matrices Under Elevated Pressure and the Techniques Employed to Measure Them -- 7. Food Processing by High Pressure Homogenization -- 8. Pressure Shift Freezing and Thawing -- 9. Pulsed High Pressure -- 10. Applications and Opportunities for Pressure-Assisted Extraction -- 11. High Pressure in Combination with High Temperature and Other Preservation Factors -- 12. Modeling High Pressure Processes-Equipment Design, Process Performance Evaluation and Validation -- 13. High Pressure Processing Uniformity -- 14. Microbiological Aspects of High Pressure Food Processing: Inactivation of Vegetative Microorganisms and Spores -- 15. High Pressure Effects on Viruses -- 16. High Pressure Inactivation of Transmissible Spongiform Encephalopathy Agents (Prions) in Processed Meats -- 17. Mathematical Models Based on Transition State Theory for the Microbial Safety of Foods by High Pressure -- 18. Pressure Effects on Food Proteins -- 19. Effects of High Pressure on Enzymes -- 20. Pressure Gelatinization of Starch -- 21. Reaction Chemistry at High Pressure and High Temperature -- 22. Effect of High Pressure Processing on Bioactive Compounds -- 23. Structural Changes in Foods Caused by High Pressure Processing -- Section 6. High Pressure Applications in Various Food Industry Sectors -- 24. High Pressure Effects on Fruits and Vegetables -- 25. Processing Dairy Products Utilizing High Pressure -- 26. Processing of Meat Products Utilizing High Pressure -- 27. Pressure Effects on Seafoods -- 28. Egg-Based Product Development for High Pressure Processes at Low and High Temperature -- Section 7. Regulatory and Consumer Acceptance -- 29. Pressure-Assisted Thermal Sterilization Validation -- 30. European Regulations -- 31. Consumer Acceptance of High-Pressure Processed Products -- Index.
Keywords: Food science; Food Science